A Study of Factors Affecting Purchase Intention of High-class Condominium of Generation Z Customers in Bangkok, Thailand - Yang, Ye; Preecha Methavasaraphak (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Purpose: This research attempts to study factors affecting purchase intention of high-class condominium real estate of Generation Z customers in Bangkok, Thailand based on online questionnaires. Research design, data, and methodology: The quantitative data are collected via online questionnaires, those questionnaires were distributed to Thai and Non-Thai who are aged between 20-30, income at least above 30,000 baht/month, and accommodate or plan to stay in Bangkok, Thailand within the next 2 years. The researcher collected 400 valid questionnaires and use statistical procedures to analyse the data. Four factors influence the purchase intention of high-class condominium of Generation Z customers in Bangkok, Thailand which include location, financial concern, environmental concern, and perceived value. Result: There are three factors affect purchase intention of Generation Z customers to buy a high-class condominium, and those three factors are financial concern, environmental concern, and perceived value. The result can be explained as the variation of 24.1% (R2 =.241) affecting purchase intention of high-class condominium of Generation Z customers in Bangkok, Thailand. Conclusion: Ye Yang found out that the perceived value is the most important factor which affect purchase intention of high-class condominium of Generation Z customers in Bangkok, Thailand, follow by perceived value, environmental concern, and location respectively.